Analysis of physical education lessons in the aspect of its organization, teacher’s work and attitudes as well as attitudes of students on the example of participant observation - Madejski, Eligiusz (Health Promotion & Physical Activity, 2020)
Introduction: The lesson as the basic methodical unit is the most important link in the process of physical education. The aim of the research was to learn the organization and course of physical activities in early school teaching, teacher's work and attitudes, and students' attitudes towards lessons. Material and methods: The research used focused, public participant observation, which covered 128 lesson units in 19 randomly selected primary schools in Krakow. To describe the obtained qualitative data, the statement of numbers and percentages and the percent chart were used. Results: Most physical education lessons were held in the gym. A large part of physical activities were carried out contrary to the principles of building the lesson. There was also a lack of individualization of requirements for students, the use of praise and grades for correctly performed exercises, and the enforcement of instructions given to students. Almost half the lesson was unattractive. During the classes very good treatment of students by teachers was visible. Conclusions: In addition to well-conducted preparatory activities before PE, a number of organizational and methodological errors were noted. Teachers' attitudes towards tasks related to conducting physical activities were not satisfactory. The attitude of students to the duties related to participation in physical education lessons was positive.